Daily field checking list by Walter Rosene, March 22, 1936 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, Walter Rosene, Jr. and Bob Walker, March 22, 1936. Also notes they traveled to various ponds. Plustek--flatbed